Spin Entangled State Transfer in Quantum Dot Arrays: Coherent Adiabatic and Speed‐Up Protocols. Issue 10 (29th July 2019) - Ban, Yue; Chen, Xi; Kohler, Sigmund; Platero, Gloria
Abstract: Long‐distance transfer of quantum states is an indispensable part of large‐scale quantum information processing. A novel scheme for the transfer of two‐electron entangled states from one edge of a quantum dot array to the other by coherent adiabatic passage is proposed. This protocol is mediated by pulsed tunneling barriers. In a second step, a speed up is sought for by shortcut to adiabaticity techniques. This significantly reduces the operation time and, thus, minimizes the impact of decoherence. For typical parameters of state‐of‐the‐art solid state devices, the accelerated protocol has an operation time in the nanosecond range and terminates before a major coherence loss sets in. The scheme represents a promising candidate for entanglement transfer in solid state quantum information processing. Abstract : A protocol is provided to transfer entangled states in quantum dot arrays by adiabatic passage, which can be accelerated in the timescale of nanoseconds by shortcuts to adiabaticity. The feasibility of the proposed protocol with numerical studies, including non‐ideal conditions such as imperfect pulses and decoherence is demonstrated. Moreover, the protocol can be implemented with cold atoms and photonic crystals.